THE EFFECT OF BAGASSE FIBER (Saccharum officinarum L.) ADDITION ON THE COMPRESSIVE STRENGTH OF BULK FILL COMPOSITE RESIN - Thamara, Citra Aghnia; Erlita, Isyana; Diana, Sherli (Dentino, 2018)
Background: Bulk fill composite resin is a composite resin with 4 mm filling technique in one application and lighting in one time. This material commonly used for posterior teeth restoration, so good compressive strength is needed. The increase in compressive strength in restoration can be used with addition of synthetic fiber or natural fiber. Natural fiber that can be used is bagasse fiber. Purpose: To acknowladge the influence of bagasse fiber addition to the compressive strength of bulk fill composite resin. Methode: This study was a true experimental study with posttest only control group design. The total of the sample was 24 samples that were divided into 3 groups, which consisted of: group 1 bulk fill composite resin with addition of bagasse fiber, group 2 bulk fill composite resin with addition of synthetic fiber and group 3 bulk fill composite resin without addition of fiber. The measurement of compressive strength used universal testing machine. Result: The average value of compressive strength of group 1 was 353,466 MPa, group 2 was 364,583 MPa and group 3 was 348,698 MPa. The result of parametric One Way ANOVA test was p=0,000 (p<0,05) and continued with Post Hoc Bonferroni test showed that there was significant difference between each groups (p<0,05). Conclusion: The addition of bagasse fiber influence the compressive strength of bulk fill composite resin higher than those without the addition of bagasse fiber, but it is still lower if compared with the addition of synthetic fiber.